Development and Validation of a New Clinical Prediction Model of Catheter-Related Thrombosis Based on Vascular Ultrasound Diagnosis in Cancer Patients - Liu, Binliang; Xie, Junying; Sun, Xiaoying; Wang, Yanfeng; Yuan, Zhong; Liu, Xiyu; Huang, Zhou; Wang, Jiani; Mo, Hongnan; Yi, Zongbi; Guan, Xiuwen; Li, Lixi; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: The central venous catheter brings convenience for drug delivery and improves comfort for cancer patients, it also causes serious complications. The most common one is catheter-related thrombosis (CRT). Objectives:This study aimed to evaluate the incidence and risk factors of CRT in cancer patients and to develop an effective prediction model for CRT in cancer patients. Methods: The development of our prediction model was based on the data of a retrospective cohort (n=3131) from National Cancer Center. The validation of our prediction model was done in a prospective cohort from National Cancer Center (n=685) and a retrospective cohort from Hunan Cancer Hospital (n=61). The predictive accuracy and the discriminative ability were determined by the receiver operating characteristic curves and calibration plots. Results: Multivariate analysis demonstrated that sex, cancer type, catheter type, position of the catheter tip, chemotherapy status, and antiplatelet/anticoagulation status at baseline were independent risk factors for CRT. The area under receiver operating characteristic (ROC) curve of our prediction model was 0.741 (CI: 0.715-0.766) in the primary cohort; 0.754 (CI: 0.704-0.803) and 0.658 (CI: 0.470-0.845) in validation cohorts respectively. Good calibration and clinical impact were also shown in primary and validation cohorts. Conclusions: Our model is a novel prediction tool for CRT risk which helps to assign cancer patients into high-risk or low-risk groups accurately. Our model will be valuable for clinicians in the decision making of thromboprophylaxis.